2020
DOI: 10.1063/5.0019832
|View full text |Cite
|
Sign up to set email alerts
|

Energy transport and light propagation mechanisms in organic single crystals

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…We visualise the spatio-temporal dynamics of singlet excitons, created by the 'singlet laser', as well as their manipulation by the triplet population using a detection-beam scanning approach combined with time-correlated single-photon counting of the prompt fluorescence signal. 10,28,31 We measure fluorescence decay curves at fixed positions of the laser foci, while scanning the detection position along the long (x-) axis of the bundle (centred around the 'singlet laser' focus). We thus create a time-dependent distribution of the prompt fluorescence of singlet excitons, I(x,t), as a function of the distance x relative to the centre of the 'singlet laser' and time t after its arrival on the sample (see Materials and methods, ESI †).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We visualise the spatio-temporal dynamics of singlet excitons, created by the 'singlet laser', as well as their manipulation by the triplet population using a detection-beam scanning approach combined with time-correlated single-photon counting of the prompt fluorescence signal. 10,28,31 We measure fluorescence decay curves at fixed positions of the laser foci, while scanning the detection position along the long (x-) axis of the bundle (centred around the 'singlet laser' focus). We thus create a time-dependent distribution of the prompt fluorescence of singlet excitons, I(x,t), as a function of the distance x relative to the centre of the 'singlet laser' and time t after its arrival on the sample (see Materials and methods, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Second, while singlet exciton transport is mediated predominantly by long-range Coulomb interactions, triplet exciton transport is driven by short-range exchange interactions. 24,26 Therefore, experimentally observed diffusivities of singlet excitons are typically two to three orders of magnitude greater than those of triplet excitons, 10,[27][28][29][30][31][32][33][34][35] i.e., triplet excitons are essentially immobile on time scales of the short (nanosecond) singlet exciton lifetime. Finally, contrary to singlet-singlet or triplet-triplet annihilation, after singlet-triplet annihilation an excited triplet state survives due to spin conservation: 24…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These long transport distances and high diffusion constants are rather surprizing for self-assembled organic structures with unavoidable electronic and structural disorder. It is even more surprizing considering that these transport distances of singlet excitons exceed those commonly observed in highly ordered organic single crystals 10 as well as in (semicrystalline) organic thin films by sometimes more than two orders of magnitude [111,[113][114][115][116][117][118]. The origin of these long distances in supramolecular nanostructures is not entirely clear yet and subject to on-going discussions [10], in particular, since micrometre transport has been demonstrated on both J-and H-type nanostructures.…”
Section: General Aspects Of Long-range Energy Transport In (Individual) Supramolecular Nanostructuresmentioning
confidence: 99%
“…A recent development in the experimental study of excitons has been the combination of high spatial resolution with the time-resolved methods described above. This spatial resolution can be directly implemented using microscopy techniques, as described by Wittmann et al 10 in their studies of the subdiffusive transport of singlet excitons in oligothiophene crystals. Alternatively, Kunsel et al 11 showed how single molecule measurements on Zn-chlorophyll aggregates can be analyzed to provide detailed information on correlated disorder on 10 nm length scales.…”
Section: A Experimental Tools For Excitonsmentioning
confidence: 99%